A meta-analysis supports core needle biopsy by radiologists for better histological diagnosis in soft tissue and bone sarcomas. Issue 29 (July 2018) - Kubo, Tadahiko; Furuta, Taisuke; Johan, Muhammad P.; Sakuda, Tomohiko; Ochi, Mitsuo; Adachi, Nobuo
Abstract: Background: Although surgical biopsy has historically been considered to be the standard diagnostic biopsy for soft tissue and bone sarcomas, recent literature suggests that percutaneous core needle biopsy yields similar results. Therefore, an evaluation of the exact diagnostic accuracy and associated influential variables of core needle biopsy that is based on a large data set would be useful. Methods: We searched MEDLINE, Web of Science, and EMBASE to identify core needle biopsy studies for predicting final histological subtypes of musculoskeletal lesions. The diagnostic accuracies of core needle biopsy and of surgical biopsy were assessed and compared by using random-effect meta-analyses. The factors relevant to diagnostic accuracy were evaluated by meta-regression and subgroup analyses. Results: We selected 32 studies comprising 7209 musculoskeletal lesions. The pooled proportion estimate for the diagnostic accuracy of core needle biopsy was 0.84 (95% confidential interval, CI: 0.81–0.87), which indicated an approximate 84% concordance between core needle biopsy results and final histological diagnoses. The findings of meta-regression and subgroup analyses suggested that radiologists were better core needle biopsy operators than surgeons. An additional meta-analysis for direct comparison between core needle biopsy and surgical biopsy demonstrated that diagnostic accuracy was significantly lower for core needle biopsy than for surgical (pooled odds ratio: 0.39, 95% CI: 0.20–0.76). Conclusion: Our results suggested that core needle biopsy should be performed by expert radiologists and that surgical biopsy should be performed if diagnosis following core needle biopsy does not match the clinical presentation and radiographic findings